2008
DOI: 10.1007/s10750-008-9530-x
|View full text |Cite
|
Sign up to set email alerts
|

Realism of model ecosystems: an evaluation of physicochemistry and macroinvertebrate assemblages in artificial streams

Abstract: Ecological realism is an important yet rarely reported feature of model ecosystems. In this case study, we assess the realism of four outdoor artificial stream mesocosms (4 m 2 ) bordering a chalk river in southern England. Comparisons of physiochemical conditions and benthic macroinvertebrate assemblages were made between the mesocosm units and the parent water body, a side arm of the River Frome. Physicochemistry of the mesocosm replicates was similar to that of the source stream, with congruent temporal var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
51
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(57 citation statements)
references
References 51 publications
6
51
0
Order By: Relevance
“…We therefore believe that diversity in experimental flumes maybe generally lower than in natural stream ecosystems, such as was the case in our experiments. Also Ledger et al (2009) reported less taxa in the flumes than in the stream. This should mean that many flume experiments may lack "ecological realism" (Ledger et al, 2009).…”
Section: Differences In Invertebrate and Periphyton Composition Betwementioning
confidence: 92%
See 2 more Smart Citations
“…We therefore believe that diversity in experimental flumes maybe generally lower than in natural stream ecosystems, such as was the case in our experiments. Also Ledger et al (2009) reported less taxa in the flumes than in the stream. This should mean that many flume experiments may lack "ecological realism" (Ledger et al, 2009).…”
Section: Differences In Invertebrate and Periphyton Composition Betwementioning
confidence: 92%
“…Also Ledger et al (2009) reported less taxa in the flumes than in the stream. This should mean that many flume experiments may lack "ecological realism" (Ledger et al, 2009). Experiments are necessary in order to deduce causal relationships, since these cannot be inferred from correlative field data.…”
Section: Differences In Invertebrate and Periphyton Composition Betwementioning
confidence: 92%
See 1 more Smart Citation
“…18). These model systems reflected the abiotic conditions, biodiversity and food web properties of natural streams Harris et al, 2007;Ledger et al, 2009). The results of this fragmentation experiment revealed some dramatic impacts on the food webs: consistent with the higher trophic rank hypothesis (e.g.…”
Section: Box 8 Fragmentation Of Mountainous Aquatic Food Websmentioning
confidence: 99%
“…Besides food webs, several examples from other multitrophic systems give an indication of how antagonistic host-parasitoid networks may be affected by fragmentation (Cronin, 2004;Kruess, 2003;Thies et al, 2005 Figure 18 Impacts of habitat fragmentation caused by drought in experimental stream food webs: results from a long-term field experiment in artificial streams Ledger et al, 2008Ledger et al, , 2009Ledger et al, , 2011. Drought can have patchy effects in river networks and individual stream channels can be viewed as fragmented patches in the wider riverscape.…”
Section: Antagonistic Host-parasitoid Networkmentioning
confidence: 99%